Peningkatan Kapasitas Forum Pengurangan Resiko Bencana dalam Kerangka Desa Tangguh Bencana di Desa Citimun Kecamatan Cimalaka Kabupaten Sumedang - Hikmat Pramajati; Nunung Siti Sukaesih; Emi Lindayani; Iyos Sutresna; Ahmad Purnama (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Natural disasters are natural phenomena that directly or indirectly disrupt human life and can occur at any time. Therefore, community preparedness is necessary to face disasters, considering that most Indonesians live in disaster-prone areas. As part of the Disaster Resilient Village Program, the Village Disaster Risk Reduction Forum (FPRB) functions to advocate, coordinate, and implement collaborative disaster risk reduction efforts at the village level. The goal is to ensure disaster risk reduction-based development, increase community resilience, and disaster preparedness. FPRB must have the ability to recognize threats in their area, be able to organize resources to reduce vulnerability and increase capacity to reduce disaster risk, and achieve disaster preparedness. Therefore, there is a need for mentoring and capacity building in preparing communities, particularly in terms of strategies, knowledge, and skills, as part of disaster preparedness. The application of this community service program aims to provide training and mentoring for members of the village disaster risk reduction forum, including the preparation of disaster risk assessments, emergency response plans, contingency plans, and basic life support. This service was attended by members of the village disaster risk reduction forum and village government officials, which was held from April to October 2025. The external targets in this study are the disaster management plan documents in the village, which include disaster risk assessments, emergency response plans, standard operating procedures, and post-disaster contingency plans and the skills of the FPRB members in providing first aid to disaster victims.